Think-aloud technique and protocol analysis in clinical decision-making research - Lundgrén-Laine, Heljä; Salanterä, Sanna (Qualitative health research, 2010)
In this article, we aim to describe the practical aspects of research actions that should be taken into account when two methods--the think-aloud technique for data collection and protocol analysis as an analysis technique--are combined with research of decision making in acute clinical settings. These methods are rarely used together or written about in health care research. In addition, careful consideration of the pros and cons of study sampling, data collection, data management, and analysis techniques or approaches is still lacking when these methods are used in health care research. We discuss the background of the think-aloud technique and protocol analysis and review previous studies that have used these methods. The examples in the article are based on our study, in which we investigated the decision making of critical care experts. We find that the combination of the think-aloud technique and protocol analysis is applicable when investigating complex and overlapping decision-making processes and rapid, ad hoc decisions made by critical care experts.